2015
DOI: 10.1371/journal.pntd.0003923
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Infection and Immune Responses in Lutzomyia longipalpis Sand Fly Larvae Midgut

Abstract: The midgut microbial community in insect vectors of disease is crucial for an effective immune response against infection with various human and animal pathogens. Depending on the aspects of their development, insects can acquire microbes present in soil, water, and plants. Sand flies are major vectors of leishmaniasis, and shown to harbor a wide variety of Gram-negative and Gram-positive bacteria. Sand fly larval stages acquire microorganisms from the soil, and the abundance and distribution of these microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Combating other diseases or pests with the use of paratransgenesis. Pantoea agglomerans also occurs commonly in the gut of sand flies Lutzomyia longipalpis and Phlebotomus papatasi which are vectors of leishmaniasis, a disease caused by the protozoan parasites belonging to Leishmania genus [74,75]. Paratransgenesis with the use of P. agglomerans is therefore also considered in the case of this vector-borne disease.…”
Section: Fighting Of Diseases Transmitted By Arthropod Vectors and Armentioning
confidence: 99%
“…Combating other diseases or pests with the use of paratransgenesis. Pantoea agglomerans also occurs commonly in the gut of sand flies Lutzomyia longipalpis and Phlebotomus papatasi which are vectors of leishmaniasis, a disease caused by the protozoan parasites belonging to Leishmania genus [74,75]. Paratransgenesis with the use of P. agglomerans is therefore also considered in the case of this vector-borne disease.…”
Section: Fighting Of Diseases Transmitted By Arthropod Vectors and Armentioning
confidence: 99%
“…perfiliewi and Lutzomyia longipalpis 78910111213141516. Regarding the microbial contributions to the physiology of sand flies, gut bacteria have been shown to play roles in development17 and immunity1819. In addition, evidence has become available that resident microorganisms in the gut are able to inhibit Leishmania infections2021.…”
mentioning
confidence: 99%
“…Telleria et al (2013) reported that L. longipalpis modulates defensin expression upon bacterial and Leishmania infection, with patterns of expression that are distinct among bacterial species and routes of infection. Also, Heerman et al (2015) stated the midgut microbial community in insect vectors of disease proved crucial for an effective immune response against infection with various human and animal pathogens. They added that that during development, the sand flies harbor a wide variety of Gram-negative and Gram-positive bacteria, acquired as larval stages from the soil, and the abundance and distribution of these microorganisms varied depending on the sand fly species or the breeding site.…”
Section: Review and Discussionmentioning
confidence: 99%